Simulação de ocorrência de falha em material de resíduo de construção civil álcali-ativado em modelo de peça impressa usando parâmetros obtidos por excitação por impulso - Albuquerque, Lucas Mendes Carneiro de (2022)
The objective of this work is to characterize the mechanical properties of an alkali activated recycled construction waste material. This opportunity arises from the fraction of civil construction waste that is not recycled because it has amorphous properties in the state in which it is collected. By characterizing certain properties, it will be possible to carry out simulations on the material, which is composed of ceramic block powder and mixed with clay, hydrated lime, water and sodium silicate. Specimens were produced using silicone molds and molds made from PVC tubes, and with two geometry configurations: prismatic and cylindrical. The characterization of some mechanical properties was carried out by static test, according to the conventional method of traction in the 3-point bending mode and axial compression, and dynamic test, by the impulse excitation technique using the Sonelastic device. Poisson’s coefficient, elastic and shear moduli results were obtained using the impulse excitation technique. The SolidWorks program was used to simulate the mechanical resistance to compression of models obtained from the printing G-code. The model was adjusted in order to produce parts with a layer height of 2 and 5 mm. Regarding the simulations, the method was validated for a solid cylindrical specimen. Regarding the specimens generated from the G-code, all would suffer brittle fracture, according to the Mohr-Coulomb failure criterion, since the calculated main tensile and compressive stresses are greater than the properties of tensile strength and resistance to bending. Material compression.